Picturebooks as Vehicles: Creating Materials for Pedagogical Action - David Valente; Sandie MOURÃO (CLELEjournal, 2022)
The first article focuses on intercultural citizenship education and professional development with picturebooks. The paper records the highlights and challenges of an in-service and pre-service development course that formed a central part of the Erasmus+ project ICEPELL.